Current regulatory approaches for accessing potential COVID-19 therapies - Vesa Halimi; Armond Daci; Simona Stojanovska; Irina Panovska-Stavridis; Milena Stevanovic; Venko Filipce; Aleksandra Grozdanova (Taylor & Francis Group, 2020)
This commentary aims to elaborate challenges in the regulatory approaches for accessing and investigating COVID-19 potential therapies either with off-label use, compassionate use, emergency use or for clinical trials. Since no therapies have been formally approved and completely effective and safe to date, the best clinical choice is acquired only after consistent and fair communication and collaboration between licensed clinicians, researchers, regulatory authorities, manufacturers and patients.